1998
DOI: 10.1046/j.1365-313x.1998.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ADG1, an Arabidopsis locus encoding for ADPG pyrophosphorylase small subunit, demonstrates that the presence of the small subunit is required for large subunit stability

Abstract: SummaryTwo mutants of Arabidopsis have been isolated that affect ADPG pyrophosphorylase (ADGase) activity. Previously, it has been shown that ADG2 encodes the large subunit of ADGase. This study characterizes the adg1 mutant phenotype and ADG1 gene structure. RNA blot analyses indicate that the adg1-1 mutant accumulates transcripts encoding both the large and small subunits of ADGase, while the adg1-2 mutant accumulates only large subunit transcripts. RFLP analysis and complementation of adg1 mutants with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 36 publications
3
66
0
Order By: Relevance
“…The OtaL protein could not be expressed in a soluble form, possibly because it needs the S subunit for folding and solubility as demonstrated in other organisms (4,11,37). When OtaL was expressed alone, it went to the insoluble fraction after ultrasonic disruption of the cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The OtaL protein could not be expressed in a soluble form, possibly because it needs the S subunit for folding and solubility as demonstrated in other organisms (4,11,37). When OtaL was expressed alone, it went to the insoluble fraction after ultrasonic disruption of the cells.…”
Section: Resultsmentioning
confidence: 99%
“…They have good expression by themselves but have defective regulatory properties (low apparent affinity for the activator 3-PGA) (1, 2). OtaL, StuL, and Arabidopsis APL3 and APL4 isoforms confer a high apparent affinity for the activator to the heterotetramer (1, 2) but cannot fold properly by themselves (2,11,37). There are two remarkable differences between O. tauri S and L subunits and other ADP-Glc PPases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To rule out the possibility that the low rate of oil accumulation in sse1 was simply a consequence of increased carbon flux into starch, we assessed the effect of abolishing starch synthesis on the production of oil in sse1. As shown in Figure 5B, although starch accumulation was prevented by introducing the starch synthesis mutants adg1 (Lin et al, 1988;Wang et al, 1998) or pgm1 (Caspar et al, 1985, Periappuram et al, 2000 into the sse1 background, the levels of oil in the sse1adg1 or sse1pgm1 double mutants and the sse1 single mutant (all in the C24 and Col hybrid background) were indistinguishably low, less than 10% of that in wild type C24 or Col. These results demonstrated that the low rate of oil deposition in sse1 was not caused by the increased starch synthesis.…”
Section: Sse1 Developing Embryos Exhibit Reduced Rates Of Fatty Acid mentioning
confidence: 97%
“…The higher plant SS group can be divided in two subgroups: one corresponding to monocots and a second one corresponding to dicots (including APS1 from Arabidopsis). APS1 from Arabidopsis is essential to starch synthesis in vivo as revealed the study of starch-lacking mutant plants (45). Small subunits are considered to be ubiquitous, although in the case of rice, Vicia faba, and pea, for which two genes coding for …”
Section: Kinetic Parameters Of the Arabidopsis Recombinant Adp-glc Ppmentioning
confidence: 99%